Chemical profiles of venom glands in queens, foundresses, pre-wintering gynes, and workers in the hornet Vespa velutina nigrithorax - Berville, Laurence; Lucas, Christophe; Haouzi, Mélissa; Khalil, Ali; Gévar, Jérémy; Bagnères, Anne-Geneviève; Darrouzet, Eric (Comptes Rendus. Chimie)
Invasive species are permanently modifying the distribution and diversity of native species worldwide. For nearly two decades, a hornet, Vespa velutina nigrithorax (Hymenoptera: Vespidae), has been spreading in Europe. Due to its marked invasiveness, this yellow-legged hornet is of great economic and ecological concern, mainly because of the damage it causes to insects in general and bees in particular. Current management methods are sparse and ineffective. Naturally produced by insects, semio-chemicals have been proposed as integrated management tools in this context, either for disruption or mass trapping, as an alternative tool to conventional non-selective traps. Here, we focused on the venom gland, which produces the alarm pheromone. In previous studies, individuals showed marked diversity in their chemical profiles. However, to successfully conduct targeted pheromone-based trapping, the hornet’s chemical ecology must be thoroughly characterized. Therefore, it was necessary to better understand the chemical composition of the alarm pheromone of not only workers but also other V. v. nigrithorax females. First, we evaluated the differences in venom gland profiles between the four types of females: queens, foundresses, pre-winter gynes, and workers. Next, we experimentally explored the venom gland profiles of V. velutina nigrithorax workers and pre-wintering gynes by in vivo and in vitro approaches. We found 13 new compounds in the venom gland, of which 9 were identified (chain lengths: C8 to C12). Two compounds were found exclusively in reproductive females. Profiles differed among pre-wintering gynes, foundresses, and queens but not between pre-wintering gynes and workers. This result indicates that the chemical signature of the female venom gland changes over the course of life history: from pre-wintering gynes to foundresses to queens.